Equal prefrontal cortex activation between males and females in a motor tasks and different visual imagery perspectives: a functional near-infrared spectroscopy (fNIRS) study - Thiago F. Dias Kanthack; Marcelo Bigliassi; Leandro Ricardo Altimari (Universidade Estadual Paulista (UNESP), 2013)
The purpose of this study was to compare the prefrontal cortex (PFC) blood flow variation and time on in males and females while performing a motor task and imagery perspectives. Eighteen right handed subjects (11 males and 7 females) were volunteers to this study. All subjects went through three randomly conditions, a motor task condition (MT) in which they had to do a simple finger tap. The other conditions included practicing imagery in first and third views. During all the conditions, the fNIRS device was attached to the subject forehead to obtain the blood flow; the total time in each task which was measured with a chronometer. No difference had been found in any condition for both sexes in the PFC and time, nor for all subjects integrated in the PFC. Therefore, we conclu-de that both imageries can be used to mentally train a motor task, and probably both sexes can be benefited.